Peningkatan Hasil Belajar Peserta Didik Melalui Pembelajaran Kooperatif Model BBM Materi Animalia pada Kelas X.7 di SMA N 1 Sumber - A Hidayati (Universitas Sebelas Maret, 2019)
Abstract. The background of this research is the students’ of the Class X.7 learning result at low criteria. The problem statement is about how to increase the students’ of the Class X.7learning result. The purpose of this research is to increase the students’ of the Class X.7 of 1 Sumber Senior High School on Biology learning result about Animalia. The action to increase the learning result is using the BBM model (Bamboo Dancing). The result of this research showed that the average of learning result before applying the BBM model is 71,88, increased in the end of the Second Cycle on 83,29, that mean the increasing is 11,41. The completeness of learning result before applying the BBM model is 58,82%, increased in the end of the Second Cycle at 82,35%, that mean the increasing is 23,53%. On the First Cycle, the indicator of success is not reached at 80%, but on the Second Cycle increased and reached beyond of theindicator of success. According to the result of this research, the conclusion is the applying of the BBM model about Animalia is increasing the students’ of the Class X.7 of 1 Sumber Senior High School learning result on the Second Semester of the 2016/2017 Year Academic.